Equalizing access : affirmative action in higher education in India, United States, and South Africa - Hasan, Zoya, 1947-; Nussbaum, Martha C. (Martha Craven), 1947- (New Delhi : Oxford University Press, 2012)
Papers presented at a conference on 'Affirmative action in higher education in India, United States, and South Africa', held at New Delhi in March 2008.
Includes bibliographical references.
Keywords: AFFIRMATIVE ACTION PROGRAMS IN EDUCATION--INDIA.; AFFIRMATIVE ACTION PROGRAMS IN EDUCATION--UNITED STATES; AFFIRMATIVE ACTION PROGRAMS IN EDUCATION--SOUTH AFRICA